A Subgrid Parameterization for Wind Turbines in Weather Prediction Models with an Application to Wind Resource Limits - B. H. Fiedler; A. S. Adams (Advances in Meteorology)
A subgrid parameterization is offered for representing wind turbines in weather prediction models. The parameterization models the drag and mixing the turbines cause in the atmosphere, as well as the electrical power production the wind causes in the wind turbines. The documentation of the parameterization is complete; it does not require knowledge of proprietary data of wind turbine characteristics. The parameterization is applied to a study of wind resource limits in a hypothetical giant wind farm. The simulated production density was found not to exceed 1 W m−2, peaking at a deployed capacity density of 5 W m−2 and decreasing slightly as capacity density increased to 20 W m−2.